In Vivo Kinetic and Kinematic Analysis of Healthy Iliotibial Band Biomechanics. - Felipe, Jack T.; Burk, Adam M.; Duong, Katherine M.; Cone, Stephanie G. (Journal of Applied Biomechanics, 2025)
The iliotibial (IT) band is a complex structure of connective tissue with proximal origins at the tensor fasciae latae and gluteus maximus, with a distal insertion on the tibia at Gerdy's tubercle. Although there is established knowledge of IT band anatomy, its biomechanical function during active motion is poorly defined to date due to experimental challenges in the direct measurement of IT band function. In this study, we applied shear wave tensiometry, ultrasound imaging, and motion capture to assess the structure–function relationship of the IT band during a battery of functional tasks. We found that there was a high variability in IT band tension levels across participants in functional tasks, despite a lack of significant differences in joint angles at the knee or hip during the same movements. Preliminary gait data from a pilot subject revealed higher shear wave speed peaks during jogging compared with walking, as well as shifts in the timing of shear wave speed peaks corresponding to the different phases of jogging versus walking gait. Together, these findings suggest that the IT band is active in many forms of movement but highly variable between participants, potentially due to differences in both muscular activation and anatomy.